Phosphoinositide 3-kinase in Health and Disease Volume 2 - Rommel, Christian; Vanhaesebroeck, Bart.; Vogt, Peter K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
From humble beginnings over 25 years ago as a lipid kinase activity associated with certain oncoproteins, PI3K (phosphoinositide 3-kinase) has been catapulted to the forefront of drug development in cancer, immunity and thrombosis, with the first clinical trials of PI3K pathway inhibitors now in progress. Here the authors give a brief overview of some key discoveries in the PI3K area and their impact, and include thoughts on the current state of the field, and where it could go from here
Keywords: Medicine; Oncology; Biomedicine; Cancer Research